Iron deposition heterogeneity in extrapyramidal system assessed by quantitative susceptibility mapping in Parkinson’s disease patients with type 2 diabetes mellitus - Li, Wanyao; Gao, Bingbing; Du, Wei; Jiang, Yuhan; Yang, Jing; Hu, Rui; Liu, Yangyingqiu; Liu, Na; Zhang, Yukun; Song, Qingwei; Miao, Yanwei (Frontiers in Aging Neuroscience, 2022)
Purpose: Excessive brain iron depositions were found in both Parkinson’s disease (PD) and type 2 diabetes mellitus (T2DM) patients. This present study aims to explore iron deposition and heterogeneity in extrapyramidal system in PD patients with T2DM using quantitative susceptibility mapping (QSM), so as to further reveal the effect of T2DM on the changes of brain iron in PD patients. Materials and Methods: Thirty-eight PD with T2DM (PDDM) patients, thirty PD without T2DM (PDND) patients and twenty control subjects (CSs) were recruited in this study. All subjects underwent multiple MRI sequences involving enhanced gradient echo T2 star weighted angiography (ESWAN). The magnetic sensitivity values (MSV) and volume of the whole nuclei (MSV W, VW) and high iron region (MSV R II, VR II) were measured on bilateral caudate nucleus (CN), putamen (PUT), globus pallidus (GP), substantia nigra (SN), red nucleus (RN) and dentate nucleus (DN). Clinical and laboratory data were recorded, especially for Hoehn and Yahr (H-Y) stage, Montreal Cognitive Assessment (MoCA), Mini-mental State Examination (MMSE), Hamilton depression scale (HAMD) and Hamilton anxiety scale (HAMA). Then all QSM data was compared between PDDM and PDND patients, and correlated with clinical and laboratory data. Results: The H-Y stage of PDDM group was higher than that of PDND group. Higher MSVW and MSVR II were found in PDDM group compared to PDDN group, especially for significant differences in bilateral SN of MSVW and bilateral CN, right PUT, bilateral GP, bilateral SN of MSVR II. Compared with the PDND group, the VR II / VW of the left CN was significantly increased in the PDDM group. The MSVR II of bilateral RN in PDDM group were positive correlation with the HAMA scores. Decreased HDL levels, decreased DBP levels and increased SBP levels were associated with a increased MSVR II of right CN in PDDM. Conclusion: The distribution of brain iron in PD patients with T2DM was significantly heterogeneous. T2DM can aggravate the disease severity and anxiety in PD patients. Effective management of blood pressure and blood lipids level during PDDM progression offers an important strategy for the treatment of this disease.